2008
DOI: 10.4137/cin.s408
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Microarray-based Classifiers: An Overview

Abstract: For the last eight years, microarray-based class prediction has been the subject of numerous publications in medicine, bioinformatics and statistics journals. However, in many articles, the assessment of classifi cation accuracy is carried out using suboptimal procedures and is not paid much attention. In this paper, we carefully review various statistical aspects of classifi er evaluation and validation from a practical point of view. The main topics addressed are accuracy measures, error rate estimation proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0
9

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(87 citation statements)
references
References 113 publications
(161 reference statements)
2
76
0
9
Order By: Relevance
“…The characteristics of the two datasets are represented in table 1, the number of iterations used to compute the test error rate with a Monte Carlo Cross Validation algorithm [3] is fixed to B = 50. …”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of the two datasets are represented in table 1, the number of iterations used to compute the test error rate with a Monte Carlo Cross Validation algorithm [3] is fixed to B = 50. …”
Section: Resultsmentioning
confidence: 99%
“…However, the choice of filtering methods and their tuning are still among open questions in high dimensional classification with PLS. The literature on variable filtering is rich with many pros and cons for both univariate and multivariate filtering approaches (Boulesteix et al 2008). Boulesteix (2004) observed that PLSDA reached best classification accuracy with more than one PLS component and suggested that Proof.…”
Section: Discussionmentioning
confidence: 99%
“…response to treatment or disease course, and molecular diagnosis [21] as well as an algorithm-oriented approach to extracting the variables responsible for class separation and prediction. Common univariate methods like t-tests and Wilcoxon tests "are fast and conceptually simple.…”
Section: Classification With Variable Selectionmentioning
confidence: 99%
“…Common univariate methods like t-tests and Wilcoxon tests "are fast and conceptually simple. However, they do not take correlations and interactions between variables into consideration, resulting in a subset of variables that may not be optimal for classification" [21] . Multivariate variable selection approaches, on the other hand, recognize that the subset of variables with best univariate discrimination power are not necessarily the best subset of classification variables, and try to determine which combinations of variables yield high prediction accuracies.…”
Section: Classification With Variable Selectionmentioning
confidence: 99%